Environmental Control of Phosphorus Acquisition: A Piece of the Molecular Framework Underlying Nutritional Homeostasis. (28th January 2021) - Ueda, Yoshiaki; Sakuraba, Yasuhito; Yanagisawa, Shuichi
Abstract: Homeostasis of phosphorus (P), an essential macronutrient, is vital for plant growth under diverse environmental conditions. Although plants acquire P from the soil as inorganic phosphate (Pi), its availability is generally limited. Therefore, plants employ mechanisms involving various Pi transporters that facilitate efficient Pi uptake against a steep concentration gradient across the plant–soil interface. Among the different types of Pi transporters in plants, some members of the PHOSPHATE TRANSPORTER 1 (PHT1) family, present in the plasma membrane of root epidermal cells and root hairs, are chiefly responsible for Pi uptake from the rhizosphere. Therefore, accurate regulation of PHT1 expression is crucial for the maintenance of P homeostasis. Previous investigations positioned the Pi-dependent posttranslational regulation of PHOSPHATE STARVATION RESPONSE 1 (PHR1) transcription factor activity at the center of the regulatory mechanism controlling PHT1 expression and P homeostasis; however, recent studies indicate that several other factors also regulate the expression of PHT1 to modulate P acquisition and sustain P homeostasis against environmental fluctuations. Together with PHR1, several transcription factors that mediate the availability of other nutrients (such as nitrogen and zinc), light, and stress signals form an intricate transcriptional network to maintain P homeostasis under highly diverse environments. In this review, we summarize this intricate transcriptional network for the maintenance of P homeostasis under different environmental conditions, with a main focus on the mechanisms identified in Arabidopsis.